Using coronary calcification to exclude an ischemic etiology for cardiomyopathy: A validation study and systematic review. (1st March 2017) - Premaratne, Manuja; Shamsaei, Mohabbat; Chow, Jonathan D.H.; Haddad, Tony; Erthal, Fernanda; Curran, Helen; Yam, Yeung; Szczotka, Agnieszka; Mielniczuk, Lisa; Wells, George A.; Beanlands, Rob S.; Hossain, Alomgir; et al.
Abstract: Background: Preliminary data suggests the absence of coronary artery calcification (CAC) excludes ischemic etiologies of cardiomyopathy. We prospectively validate and perform a systematic review to determine the utility of an Agatston score = 0 to exclude the diagnosis of ischemic cardiomyopathy. Methods and results: Patients with newly diagnosed LV dysfunction were prospectively enrolled. Patients underwent CAC imaging and were followed until an etiologic diagnosis of cardiomyopathy was made. Eighty-two patients were enrolled in the study and underwent CAC imaging with 81.7% patients having non-ischemic cardiomyopathy. An Agatston score = 0 successfully excluded an ischemic etiology for cardiomyopathy with a specificity of 100% (CI: 74.7–100%) and a positive predictive value of 100% (CI: 85.0%–100%). A systematic literature review was performed and studies were deemed suitable for inclusion if: 1) patients with CHF, cardiomyopathy or LV dysfunction were enrolled, 2) underwent CAC imaging and patients were assessed for an Agatston score = 0 or the absence of CAC, and 3) the final etiologic diagnosis (ischemic or non-ischemic) was provided. Eight studies provided sufficient information to calculate operating characteristics for an Agatston score = 0 and were combined with our validation cohort for a total of 754 patients. An Agatston score = 0 excluded ischemic cardiomyopathy with specificity and positive predictive values of 98.4% (CI: 95.6–99.5%), and 98.3% (CI: 95.5–99.5%), respectively. Conclusions: In patients with cardiomyopathy of unknown etiology, an Agatston score = 0 appears to rule out an ischemic etiology. A screening CAC may be a simple and cost-effective method of triaging patients, identifying those who do and do not need additional CAD investigations. Highlights: Agatston score = 0 excluded ischemic cardiomyopathy with high specificity and positive predictive values. In patients with CHF of unknown etiology, an Agatston score = 0 appears to rule out an ischemic etiology. CAC may be a simple and cost-effective method of triaging CHF patients